“ASSESSMENT OF HYPOGLYCEMIC CONDITIONS IN PATIENTS WITH TYPE 1 AND TYPE 2 DIABETES MELLITUS USING A QUESTIONNAIRECSP-DM-HYPOGL (COMPREHENSIVE SYMPTOM PROFILE-DIABETES MELLITUS HYPOGLYCEMIA MODULE)" - Urmanova Yu.M; Bolshakova S.V; Khodzhaeva F.S (Scholar Express Journals, 2024)
to study the value of the CSP-DM-HypoGl (Comprehensive Symptom Profile-Diabetes Mellitus Hypoglycemia Module) questionnaire in patients with type 1 and type 2 diabetes mellitus according to negotiability data
Keywords: hypoglycemia; diabetes mellitus type 1 and 2; questionnaire